Coaching and mentoring : a critical text - Western, Simon (SAGE, 2012)
Coaching claims to liberate creativity but can also entrap us by individualising social experience. This book brings a critical perspective on coaching and mentoring, challenging normative assumptions and narratives, and proposing a more ethical and emancipatory approach.- Resumé vydavatel
Keywords: koučování; mentorství; zaměstnanci; personal coaching; mentoring; employees; elektronické knihy; monografie; electronic books; monographs